Communication Strategy of Cyberculture-Based Religious Leaders in Creating Religious Harmony in Multicultural Communities in Medan City - Rambe, Elismayanti; Novebri, Novebri; Pratiwi, Resdilla (Ishlah: Jurnal Ilmu Ushuluddin, Adab dan Dakwah, 2022)
This research deals with communication strategies of religious leaders based on cyberculture. The aims of this study are to explore the communication strategies of religious leaders based on cyberculture in achieving religious harmony for a multicultural society in Medan, to know the effectiveness of religious leaders based on cyberculture, the last to investigate the defiance of religious leaders in achieving religious harmony for a multicultural society. The study was designed in qualitative research, which the data of this study was the association of Religious Harmony (FKUB), for collecting the data, the researcher uses interview, observation, and documentation, then it’s analyzed in four steps, they are data reduction, data display, data collection, Verifying. Based on analysis data it is found that there are some social media that have been used by religious leaders as the communication strategies in achieving religious harmony, namely: Website, TV, YouTube, Facebook, Instagram, Zoom Meeting. Those will be used by them to deliver their religious message and create mutual tolerance in the society. In addition, these communication strategies are very effective in maintaining religious harmony surrounding multicultural environments, so Medan obtained the appreciation in the Harmony Award. Lastly, the defiance of religious leaders in achieving religious harmony in Medan city is quiet enough and lacks complexities, it is based on the fact that religious tolerance is very splendid among multicultural societies.